Correction: Electronic and transport properties of Li-doped NiO epitaxial thin films. Issue 15 (22nd March 2018) - Zhang, J. Y.; Li, W. W.; Hoye, R. L. Z.; MacManus-Driscoll, J. L.; Budde, M.; Bierwagen, O.; Wang, L.; Du, Y.; Wahila, M. J.; Piper, L. F. J.; Lee, T.-L.; Edwards, H. J.; et al.
Abstract : Correction for 'Electronic and transport properties of Li-doped NiO epitaxial thin films' by J. Y. Zhang et al., J. Mater. Chem. C, 2018, 6, 2275–2282.